2020
DOI: 10.1093/cz/zoaa030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term overlap of social and genetic structure in free-ranging house mice reveals dynamic seasonal and group size effects

Abstract: Associating with relatives in social groups can bring benefits such as reduced risk of aggression and increased likelihood of cooperation. Competition among relatives over limited resources, on the other hand, can induce individuals to alter their patterns of association. Population density might further affect the costs and benefits of associating with relatives by altering resource competition or by changing the structure of social groups; preventing easy association with relatives. Consequently, the overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…2020 ). Evans et al. (2020) observed seasonal differences in how the multilayer social structure of mice ( Mus musculus domesticus ) related to genetic structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020 ). Evans et al. (2020) observed seasonal differences in how the multilayer social structure of mice ( Mus musculus domesticus ) related to genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The emergent relationship between habitat and sociality has been explored by the temporal distribution and phenology of resources and use of social information in multilayer networks (e.g., Evans et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of v-measure fluctuated between winter and summer. These changes in the importance of space use for interactions may be related to changes in mouse social behaviour during periods of high breeding activity in the summer, or in the need for increased thermoregulation in winter (Evans, Lindholm, & König, 2020; König & Lindholm, 2012). Our results therefore raise interesting questions, such as how the tendency for spatial structure to influence social interactions varies over time.…”
Section: Discussionmentioning
confidence: 99%
“…Such pairwise measures can be represented in matrix form and therefore be incorporated into a multilayer network analysis. Equipped with long-term, high-resolution data on genetic relatedness and social associations within a free-ranging population of house mice Mus musculus domesticus , Evans et al. (2021) used multilayer network techniques to investigate the relationship between genetic relatedness and social structure within and across years.…”
Section: The Promise Of Multilayer Network Analysismentioning
confidence: 99%
“…The authors also observed reduced overlap between the genetic and social layers as population density increased, suggesting that as the intensity of resource competition increased individuals modified their interaction patterns to avoid associating with relatives. The approaches used by Evans et al. (2021) are broadly applicable and provide a promising means to investigate the links between social interactions and genetic relatedness.…”
Section: The Promise Of Multilayer Network Analysismentioning
confidence: 99%